2019
DOI: 10.3390/app9163419
|View full text |Cite
|
Sign up to set email alerts
|

Novel Hand Gesture Alert System

Abstract: . Sexual assault can cause great societal damage, with negative socio-economic, mental, sexual, physical and reproductive consequences. According to the Eurostat, the number of crimes increased in the European Union between 2008 and 2016. However, despite the increase in security tools such as cameras, it is usually difficult to know if an individual is subject to an assault based on his or her posture. Hand gestures are seen by many as the natural means of nonverbal communication when interacting with a compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…They implemented both static and dynamic gestures recorded on a video and attained an accuracy of 97.68%. Mambou et al [46] suggested a sexual assault alert system from various scenes at night. The model was implemented on a combination of YOLO and CNN architecture.…”
Section: Related Workmentioning
confidence: 99%
“…They implemented both static and dynamic gestures recorded on a video and attained an accuracy of 97.68%. Mambou et al [46] suggested a sexual assault alert system from various scenes at night. The model was implemented on a combination of YOLO and CNN architecture.…”
Section: Related Workmentioning
confidence: 99%
“…With the advent of the era of artificial intelligence, human gesture recognition is attracting increasing attention due to its various applications, such as intelligent human-computer interactions [1], smart security [2], assisted driving [3], entertainment [4], smart home [5][6], competent medical care [7][8], and patient health monitoring [9]. Various human gesture recognition methods have been proposed, mainly classified as wearable and non-contact sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Hand gesture recognition is the process of detecting and classifying human hands into several categories. This task is one of the fundamental blocks in many applications such as human-robot interaction [7], video games [6], sign language interpretation [5], security and surveillance [8]. The issue of hand gesture recognition is solved by traditional methods, usually using sophisticated and expensive RGB and depth cameras.…”
Section: Introductionmentioning
confidence: 99%